Primary school teachers' emotions, implicit beliefs, and self-efficacy during the COVID-19 pandemic - Nicolosi, Simona; Alba, Martina; Pitrolo, Carmelo (Frontiers in Sports and Active Living, 2023)
During the Covid-19 pandemic, primary school teachers faced many challenges when providing online and hybrid teaching, especially in PE classes. This study aimed to analyze emotions, self-perceived instructional competence, and incremental beliefs during the first lockdown, in distance education instructional delivery, and, as the pandemic emergency persisted, in hybrid teaching. One hundred and four primary school teachers (Males = 7; Females = 97; Mage = 53.24; SDage = 7.34) were involved in the study from four Italian Primary Schools. Participants filled in the Motivation, Emotion, Strategies, and Teaching questionnaire (MESI) ( 1) administered in an online survey. Results showed that younger teachers had significantly lower scores in negative emotions when they taught than the older ones. On the other hand, older teachers have more belief in their own abilities to improve teaching, unlike younger teachers. Multivariate regression analysis indicated that teachers' positive emotions experienced in teaching predict perceived instructional efficacy during distance learning. Furthermore, teachers' positive emotions experienced in teaching and in the role of teacher predict teachers' changes in PE teaching during distance learning. Incremental beliefs predict perceived instructional efficacy during distance learning. Efforts on pre-service and in-service teacher training programs could help teachers strengthen emotional competencies and manage their stress in the classroom, both in normal educational contexts and in adverse conditions.